STUDY REGARDING THE CORRELATION BETWEEN SOMATO-FUNCTIONAL INDICES AND PHYSICAL ABILITIES TO 31-40 YEARS OLD WOMEN - Sorin Raţă (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Scientific research has been focused on studying the somaticfunctional and physical abilities indices level of development on women aged 31-40 years and the correlations between them. By practicing physical exercise can satisfy not only the dr